The Design of Automatic Irrigation System for Potted Plants using Soil Moisture Sensor - Hamidon, Nuramidah; Mohd Roslan, Intan Rohaini; Muhamad, Mimi Suliza; Mohd Arish, Nur Aini (Penerbit UTHM, 2020)
The quality of a good residential area can be defined as a good base in producing a sustainable environment. To achieve this matter, the housing area must be in a safe, clean and equipped with a sophisticated system to facilitate the management of the area, in line with the technological advances todays. One of the sources that helps to improve the quality of a sustainable environment is to create a plant landscape in every residential area. Plant landscapes refer to a combination of plants, soil and water that help fulfill human daily living, for example through vegetable cultivation [1]. Plants provide social, aesthetic, climate and physical, ecological and economic benefits in residential areas [2]. For residential areas with limited landscapes such as terraced houses, flats and bungalows, many potted plants are used by homeowners.